Institutionalizing segregation: Conditional cash transfers and employment choices - María Gabriela Palacio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Some claim that certain forms of social protection, conditional cash transfers in particular, result in perverse incentives for recipients in order to stay eligible for receiving benefits. This notion has a bearing on the design of social protection programmes and may undermine the political support for these programmes. This paper analyses Ecuador's conditional cash transfer programme, the Bono de Desarrollo Humano. The key finding is that concerns about perverse incentives appear largely misplaced. By examining broader patterns of institutionalization of occupational gender segregation, the role of cash transfers is found to be trivial to the deepening of informality and inactivity among recipients.
Keywords: J16; I38; 330; cash transfers; informality; employment; segregation; Ecuador